ID 18 – Electrophysiological findings in idiopathic acute polyradiculoneuritis concurrent with myasthenia gravis in a West Highland White Terrier dog. Issue 3 (March 2016) - Stanciu, G.D.; Musteata, M.; Solcan, G.
Abstract : Background: The concurrent development of idiopathic acute canine polyra-diculoneuritis (IACP) and myasthenia gravis (MG) have a rare occurrence in both veterinary and human medicine. Aim: This study describes the electrophysiological aspects of these two diseases when concurrent. Methods: The tests were carried out using the Neuropack, MEB 9400 Electrodiagnostic System, in an 11-years-old dog diagnosed with IACP based on clinical and electrophysiological findings and with positive titer for acetylcholine receptor antibodies (AChR). Results: Important indicators of IACP were positive sharp waves and complex repetitive discharges which characterized electromyogram; polyphasic action potentials with marked dispersion; signs of demyelination at electroneurography and an increase latency of F-waves. Cerebrospinal fluid had a normal number of cells with increased protein content. In addition a reduction with 18% in the amplitudes of the third compound muscle action potential (cMAP) compared to the first cMAP has been observed, indicating a postsynaptic disturbance described by repetitive nerve stimulation, suggestive for MG (AChR > 0.6 nmol/l). Conclusions: IACP may mask the clinical signs of MG. By electrodiagnostic we were able to identify concurrent junction neuropathies (as MG) in an IACP patient. The diagnosis of MG in an IACP patient will change the prognosis and standard IACP therapeutic protocols.